2017
DOI: 10.14740/cr616w
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Acute Coronary Syndrome Among Sudanese Individuals With Diabetes: A Population-Based Study

Abstract: BackgroundAcute coronary syndrome (ACS) is common with diabetes. The aim of this study was to establish prevalence and risk factors for ACS among Sudanese individuals with diabetes mellitus (DM).MethodsA descriptive cross-sectional study was conducted in Khartoum State and Atabra (North of Sudan). The data collection was performed through pretested questionnaire, in addition to measurement of lipid profile and HbA1c.ResultsAmong the 496 respondents, 234 (48.4%) were males and only 15 of them had ACS, while 255… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
3
9
0
Order By: Relevance
“…In this study, we showed the level of HbA1c and duration of diabetes are important risk factors for stroke. Several epidemiological studies in Sudan showed that high HbA1c and duration of diabetes can be associated with diabetes complications like diabetic septic foot, heart failure, retinopathy, nephropathy and ischemic heart disease [7][8][9]19,20] HTN was also one of the risk factor in our study especially with an increase in duration of diabetes. Importantly, Tagelsir et al showed that HTN and smoking in Sudanese individuals diagnosed with stroke were associated with significant changes in carotid arteries.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In this study, we showed the level of HbA1c and duration of diabetes are important risk factors for stroke. Several epidemiological studies in Sudan showed that high HbA1c and duration of diabetes can be associated with diabetes complications like diabetic septic foot, heart failure, retinopathy, nephropathy and ischemic heart disease [7][8][9]19,20] HTN was also one of the risk factor in our study especially with an increase in duration of diabetes. Importantly, Tagelsir et al showed that HTN and smoking in Sudanese individuals diagnosed with stroke were associated with significant changes in carotid arteries.…”
Section: Discussionsupporting
confidence: 53%
“…For instance, Ahmed et al found that the prevalence of acute coronary syndrome among Sudanese individuals with diabetes was 5.44% and main risk factors were HTN, an increase in age and increase in duration of diabetes. [7] The prevalence of heart failure in Sudanese individuals with diabetes was found to be 12.06% and risk factors were HTN and high cholesterol. [8] In the view of high level of uncontrolled diabetes, it is possible to predict high level of diabetes complications in Sudan.…”
Section: Introductionmentioning
confidence: 97%
“…The prevalence of ACS in the Middle East differed from one country to another. For instance, it was 6% in Saudi Arabia (at 2004), 8.3% in Egypt (at 2001) and 13% in Lebanon (at 2008) 4 . However, by 2030, this prevalence is expected to rise due to increasing rates of hypertension, DM, overweight, obesity, physical inactivity, smoking and dyslipidemia 4 …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, hypertension was found in 24% of the present series vs. 54.4% in the previous Iraqi study 6 . Diabetes mellitus is a well known absolute risk factor for ACS 4, 8. The outcome is reported to be poor even among non-diabetic ACS patients who have hyperglycemia on admission especially if associated with increased body fat 8, 9.…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 diabetes mellitus, comprises almost 90% burden of the disease and the remaining 10% are type 1 diabetes or gestational diabetes [ 3 ]. Recent reports have shown that diabetes and its related complications were major health problem in Sudan [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%